2016
DOI: 10.1007/s41105-016-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic sleep deprivation on glucose homeostasis in rats

Abstract: Epidemiological studies have shown that chronic sleep disturbances resulted in metabolic disorders. The purpose of this study was to assess the relationship between chronic sleep deprivation (CSD) and the glucose homeostasis in rats. Twenty-four rats were randomly divided into CSD group and control (CON) group. The CSD rats were intervened by a modified multiple platform method (MMPM) to establish an animal model of chronic sleep disturbances. After 3-month intervention, all rats were subjected to an intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…The changes in these protein levels may imply the impairments of the normal energy metabolism in response to CSD. The current study demonstrated weight loss in the CSD animals ( Figure 4B); this is consistent with that of several other animal experiments [4] . It has been suggested that the CSD was linked to food intake, body weight and energy expenditure, metabolic syndrome and glucose homeostasis [4] .…”
Section: Effect Of Csd On Energy Metabolismsupporting
confidence: 93%
See 1 more Smart Citation
“…The changes in these protein levels may imply the impairments of the normal energy metabolism in response to CSD. The current study demonstrated weight loss in the CSD animals ( Figure 4B); this is consistent with that of several other animal experiments [4] . It has been suggested that the CSD was linked to food intake, body weight and energy expenditure, metabolic syndrome and glucose homeostasis [4] .…”
Section: Effect Of Csd On Energy Metabolismsupporting
confidence: 93%
“…The current study demonstrated weight loss in the CSD animals ( Figure 4B); this is consistent with that of several other animal experiments [4] . It has been suggested that the CSD was linked to food intake, body weight and energy expenditure, metabolic syndrome and glucose homeostasis [4] . Additionally, CSD rat models showed several metabolic alterations such as increased energy expenditure and intense catabolism.…”
Section: Effect Of Csd On Energy Metabolismsupporting
confidence: 93%
“…Due to sleep deprivation, food ingestion was decreased (seven out of fifteen studies), or not changed (four out of fifteen), while in some studies (four studies) this behaviour was not monitored (Table 1). In the majority of the studies, a decrease in body weight gain was observed, which is suggested to be the result of increased energy expenditure (40) due to the exhausting conditions and physiological stress imposed by the extended protocols (from 18 to 20 h) of sleep deprivation (40)(41)(42)(43)(44)(45)(46)(47) . Studies observing a reduced body weight reported metabolic changes indicating a catabolic state or fasting like state, with reduced levels of glucose, low TAG, low cholesterol, low leptin levels, and in some studies accompanied by high levels of ghrelin and corticosterone (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) .…”
Section: Experimental Models Of Shift-and Night Work: What Do They Inmentioning
confidence: 99%
“…Interestingly, the majority of studies here reported have used male animals and only two studies were found that explored the response in females (42,74) . In the study by Xu et al (42) , authors do not discuss a possible difference in their outcomes associated with the sex of the animals.…”
Section: Main Contributions Of Experimental Models Limitations and Pmentioning
confidence: 99%
“…1B), which is also associated with sleep situation. 11) More importantly, salivary alpha amylase is also responsive to extended waking. On the other hand, it is well established that brain metabolism is higher during wake and rapid eye movement (REM) sleep than that in nonrapid eye movement (NREM).…”
mentioning
confidence: 99%